Turbidimetric Determination of Anionic Polyacrylamide in Low Carbon Soil Extracts. Issue 6 (1st November 2013) - Kang, Jihoon; Sowers, Tyler D.; Duckworth, Owen W.; Amoozegar, Aziz; Heitman, Joshua L.; McLaughlin, Richard A.
Abstract : Concerns over runoff water quality from agricultural lands and construction sites have led to the development of improved erosion control practices, including application of polyacrylamide (PAM). We developed a quick and reliable method for quantifying PAM in soil extracts at low carbon content by using a turbidimetric reagent, Hyamine 1622. Three high‐molecular weight anionic PAMs differing in charge density (7, 20, and 50 mol%) and five water matrices, deionized (DI) water and extracts from four different soils, were used to construct PAM calibration curves by reacting PAM solutions with hyamine and measuring turbidity development from the PAM–hyamine complex. The PAM calibration curve with DI water showed a strong linear relationship ( r 2 = 0.99), and the sensitivity (slope) of calibration curves increased with increasing PAM charge density with a detection limit of 0.4 to 0.9 mg L −1 . Identical tests with soil extracts showed the sensitivity of the hyamine method was dependent on the properties of the soil extract, primarily organic carbon concentration. Although the method was effective in mineral soils, the highest charge density PAM yielded a more reliable linear relationship ( r 2 > 0.97) and lowest detection limit (0.3 to 1.2 mg L −1 ), compared with those of the lower charge density PAMs (0.7 to 23 mg L −1 ). Our results suggest that the hyamine test could be an efficient method for quantifying PAM in environmental soil water samples as long as the organic carbon in the sample is low, such as in subsurface soil material often exposed at construction sites.